Constitutionally Tailoring Punishment - Bibas, Stephanos (2013)
Since the turn of the century, the Supreme Court has begun to regulate non-capital sentencing under the Sixth Amendment in the Apprendi line of cases (requiring jury findings of fact to justify sentence enhancements) as well as under the Eighth Amendment in the Miller and Graham line of cases (forbidding mandatory life imprisonment for juvenile defendants). Though both lines of authority sound in individual rights, in fact they are fundamentally about the structures of criminal justice. These two seemingly disparate lines of doctrine respond to structural imbalances in non-capital sentencing by promoting morally appropriate punishment judgments that are based on retail, individualized input and reflect the views and perspectives of multiple institutional actors. This new understanding illuminates how both doctrines relate to the Court’s earlier regulation of capital sentencing and how checks and balances can promote just punishment in a pluralistic system. It also underscores the need for other actors to complete the Court’s work outside the confines of rights-based judicial doctrines, by experimenting with a broader range of reforms that are not constitutionally required but rather are constitutionally inspired